Green supply chain management and firm performance: The mediating effect of green innovation - Maya Novitasari; Dian Agustia (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The purpose of this study was to assess green innovation as a mediating variable in the relationship between green supply chain management and firm performance. Design/methodology/approach: This study used the companies listed on the PROPER program for the 2010-2018 period on the Indonesia Stock Exchange. The sample collected by using purposive sampling method obtained 488 companies. The data were tested using STATA 16. Findings: The results of the analysis showed that green supply chain management had a positive effect on green innovation, green innovation had a positive effect on firm performance, and green supply chain management had no effect on firm performance. Green innovation mediated the relationship between green supply chain management and firm performance. Research limitations/implications: The limitation of this study was using companies listed on the PROPER program, so it needed to be studied by applying other companies. Besides, it only implemented green innovation, green supply chain management, and firm performance. Future studies can apply other green-related aspects and performances. Practical implications: Regarding the problem of environmental impact, companies in Indonesia can apply green innovation and green supply chain management to improve their firm performance. Companies in Indonesia are increasingly faced with pressure from stakeholders to implement green supply chain management. Social implications: It is useful for the Indonesian government in overcoming environmental impact issues by implementing green supply chain management by companies. Companies that implement green supply chain management will have an impact on increasing green innovation and firm performance. Originality/value: This study assessed the mediation of green innovation in the relationship between green supply chain management and firm performance. This indicated that here there was pressure from stakeholders to pay full attention to the environment, so that companies in Indonesia can apply green innovation and green supply chain management to improve firm performance.
Keywords: 650; green innovation; green supply chain management; firm performance